TP53 alterations in acute myeloid leukemia with complex karyotype correlate with specific copy number alterations, monosomal karyotype, and dismal outcome - Rücker, Frank Gert; Schlenk, Richard Friedrich; Bullinger, Lars; Zenz, Thorsten; Ganser, Arnold; Lichter, Peter; Döhner, Konstanze; Döhner, Hartmut (Blood, 2012)
To assess the frequency of TP53 alterations and their correlation with other genetic changes and outcome in acute myeloid leukemia with complex karyotype (CK-AML), we performed integrative analysis using TP53 mutational screening and array-based genomic profiling in 234 CK-AML. TP53 mutations were found in 141/234 (60%) and TP53 losses were identified in 94/234 (40%) CK-AML; in total, 164/234 (70%) cases had TP53 alterations. TP53-altered CK-AML were characterized by a higher degree of genomic complexity (aberrations per case, 14.30 vs. 6.16; P<.0001), and by a higher frequency of specific copy number alterations, such as -5/5q-, -7/7q-, -16/16q-, -18/18q-, +1/+1p, and +11/+11q/amp11q13~25; among CK-AML, TP53-altered more frequently exhibited a monosomal karyotype (MK). Patients with TP53 alterations were older and had significantly lower complete remission rates, inferior event-free, relapse-free, and overall survival. In multivariable analysis for overall survival, TP53 alterations, white blood cell counts, and age were the only significant factors. In conclusion, TP53 is the most frequently known altered gene in CK-AML. TP53 alterations are associated with older age, genomic complexity, specific DNA copy number alterations, MK, and dismal outcome. In multivariable analysis, TP53 alteration is the most important prognostic factor in CK-AML, outweighing all other variables, including the MK category.